Laparoscopy-assisted posterior low anterior resection of rectal cancer - Qu, Hao (BioMed Central, 2014)
BACKGROUND: Laparoscopy-assisted low anterior resection (LAR) of colorectal cancer, using a posterior surgical approach, is a difficult and controversial procedure to perform. We report successful operations on 13 patients with clear surgical margins and no serious complications. METHODS: Thirteen patients [10 males and three females, age range: 48 to 69 years (median: 61 years)] with low adenocarcinoma confirmed by preoperative colonoscopic biopsy (four stage T1; nine stage T2) were resected. The distance from inferior edge of tumor to dentate line was 2 ~ 5 cm (average: 3.4 cm). Intraperitoneal laparoscopy was performed to isolate rectosigmoid and mesocolon moving toward distal end of the tumor. Perineal operation was performed in the prone clasp-knife position. RESULTS: The circumferential resection margin (CRM) was negative in all cases. No serious postoperative complications occurred. There were four cases of perineal wound infection, two cases with superficial perineal wound dehiscence, and two cases with persistent postoperative sacral pain. All 13 patients passed the Wexner continence test and had satisfactory anal function during a mean 18-month postoperative follow-up period. CONCLUSION: Laparoscopic posterior LAR of colorectal cancer is a safe and reliable treatment for patients with low colorectal cancer, increasing the chance of anal functional recovery. TRIAL REGISTRATION: Chinese Clinical Trial Register ChiCTR-ONC-14005145. Registered 19 August 2014.